2004
DOI: 10.1002/ajmg.a.20670
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of SFTPC in infantile pulmonary alveolar proteinosis with or without fibrosing lung disease

Abstract: Pulmonary surfactant protein C (SP-C) is a highly hydrophobic peptide produced by type-II alveolar cells through the processing of a high-molecular weight precursor (pro-SP-C), that enhances surface tension and facilitates the recycling of pulmonary surfactant in vitro. Recently, two seemingly dominant-negative mutations of the pro-SP-C-encoding gene (SFTPC, MIM 178620), were reported in families with vertically-inherited interstitial lung disease (Nogee et al. [2001: N Engl J Med 344:573-579]; Thomas et al. [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
87
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 20 publications
2
87
0
1
Order By: Relevance
“…In particular, no studies have compared the full range of these diseases, to yield better estimates of variability and to examine the relative importance of biochemical determinations of their BALF levels. It has been shown that the levels of SP-C in patients with known mutations in SFTPB (17,18), SFTPC (19,20), ABCA3 (21), and TTF1 (22) are low. Thus, we hypothesized that SP-C might serve as a helpful screening tool for such and additional surfactant dysfunction disorders.…”
mentioning
confidence: 99%
“…In particular, no studies have compared the full range of these diseases, to yield better estimates of variability and to examine the relative importance of biochemical determinations of their BALF levels. It has been shown that the levels of SP-C in patients with known mutations in SFTPB (17,18), SFTPC (19,20), ABCA3 (21), and TTF1 (22) are low. Thus, we hypothesized that SP-C might serve as a helpful screening tool for such and additional surfactant dysfunction disorders.…”
mentioning
confidence: 99%
“…Although surfactant phospholipids are primarily responsible for lowering surface tension, two small hydrophobic proteins, surfactant proteins B and C (SP-B and SP-C), have key roles in regulating surfactant function and metabolism (1). SP-C deficiency and mutations in the SP-C gene (SFTPC) have been associated with both sporadic interstitial lung disease (ILD) due to de novo mutations and familial ILD inherited as autosomal dominant (2)(3)(4)(5)(6)(7)(8)(9)(10). One particular SFTPC mutation, a substitution of threonine (T) for isoleucine (I) in codon 73 (I73T) has been identified in multiple unrelated families (9 -11).…”
mentioning
confidence: 99%
“…3 In term infants, inherited mutations in the genes coding for surfactant protein-B, SFTPB (surfactant protein-B deficiency) and SFTPC have been identified as cause of respiratory failure. [4][5][6] Histopathology of surfactant protein-B deficiency resembles the adult form of alveolar proteinosis or a desquamative interstitial pneumonitis (DIP)-like pattern. 4,7 In addition to SFTPB and SFTPC mutations, inherited severe neonatal respiratory distress has recently been attributed to mutations in the ATPbinding cassette A3 transporter (ABCA3) gene.…”
mentioning
confidence: 99%